Exercising Tactically for Taming Postmeal Glucose Surges - Elsamma Chacko (Scientifica)
This review seeks to synthesize data on the timing, intensity, and duration of exercise found scattered over some 39 studies spanning 3+ decades into optimal exercise conditions for controlling postmeal glucose surges. The results show that a light aerobic exercise for 60 min or moderate activity for 20–30 min starting 30 min after meal can efficiently blunt the glucose surge, with minimal risk of hypoglycemia. Exercising at other times could lead to glucose elevation caused by counterregulation. Adding a short bout of resistance exercise of moderate intensity (60%–80%  VO2max) to the aerobic activity, 2 or 3 times a week as recommended by the current guidelines, may also help with the lowering of glucose surges. On the other hand, high-intensity exercise (>80%  VO2max) causes wide glucose fluctuations and its feasibility and efficacy for glucose regulation remain to be ascertained. Promoting the kind of physical activity that best counters postmeal hyperglycemia is crucial because hundreds of millions of diabetes patients living in developing countries and in the pockets of poverty in the West must do without medicines, supplies, and special diets. Physical activity is the one tool they may readily utilize to tame postmeal glucose surges. Exercising in this manner does not violate any of the current guidelines, which encourage exercise any time.